Physical activity interventions in children and adolescents - Ward, Dianne Stanton; Pate, Russell R.; Saunders, Ruth P. (Physical activity intervention series, 2007)
With modern conveniences and technology always beckoning, today's children are less active and more obese than ever--which leads to an ever-increasing need for more effective interventions to help them become more active. Physical Activity Interventions in Children and Adolescents addresses this problem by helping professionals in schools, health departments, recreation centers, state agencies, and not-for-profit organizations design, implement, and evaluate interventions to promote and increase physical activity among children and adolescents. Part of the Physical Activity Intervention Series, Physical Activity Interventions in Children and Adolescents provides information on current levels of youth physical activity and presents a basic understanding of the issues associated with it. The book offers a clear and reader-friendly overview of theories of behavior change that have been used in developing physical activity interventions in a variety of settings and methods for program evaluation. Specific recommendations for physical activity from various professional and health organizations are included as well. The book also provides descriptive epidemiology of youth physical activity that helps identify the changes in activity as children age; insights into the potential role of the family and the community in providing physical activity opportunities for youth; guidance for the development of collaborative relationships among agencies and organizations to promote physical activity in the community; and a review of available instruments for measuring physical activity in youth populations, including self-report instruments and step counters. Practical application of the information covered in Physical Activity Interventions in Children and Adolescents is demonstrated through real-world interventions that have been implemented in various settings. The programs were selected based on their demonstrated effectiveness, potential for success, or unique features. Strengths and weaknesses of each intervention are highlighted. In addition to the presentation of existing programs, guidelines for the development of new programs are presented. Sample worksheets serve as valuable tools in evaluating and designing interventions in areas where proven programs are not yet available. The text follows a three-part progression. Part I provides an orientation to activity in young people, describing how to change behavior and introducing the settings in which such behavior change programs might be developed. In part II, documented interventions are examined for programs in schools, community organizations, and home and health care settings. Part III explores intervention design, assisting those who want to design their own interventions for specific populations. Descriptions of program evaluation, including useful measurement instruments, are detailed as well. The result is a book that professionals can use for learning about physical activity and the role it plays in the lives of youth. It will guide readers in designing successful interventions that can change physical activity behavior for the children and adolescents with whom they work